Teaching methodologies for the training of educators for the professions - Allen, Beryl Millicent (1985)
This study investigated students in four professional groups (nurses, administrators, managers, and counsellors) and their teachers in order to identify their perceptions of the effectiveness of teaching/learning methods in meeting their personal and course objectives. Data were collected through classroom observation, in-depth interviews, and repertory grids. It was found that: 1) a wide variety of teaching/learning methods was used in the training of professional educators in the selected institutions, and the selection of methods was influenced by a combination of course objectives, learner expectations and characteristics, and teacher competence and espoused philosophy of education; 2) both staff and students across all five case studies held positive perceptions of participatory methodologies and were generally negative towards formal lectures even where they perceived lectures to be appropriate for achieving some cognitive objectives; 3) students identified interaction, negotiation, clearly defined instruction (structured activities), and feedback as essential features of methodology; and 4) the assumption of the humanistic and androgogical models that adult learners are necessarily self-directing was not upheld. It was found that adults not only expected explicit guidance from their teachers but that they needed to be taught to be self-directed learners
Keywords: Adult educators